Facing online scams: the bait of low-effort rewards among adolescents and parents - Vizcaíno-Verdú, Arantxa; Feijoo, Beatriz; Sádaba, Charo; Zozaya, Luisa (Journal of Information, Communication and Ethics in Society, 2026)
Purpose This study aims to investigate adolescents’ interactions with deceptive content on social media, focusing on scams that promise effortless rewards. Design/methodology/approach The methodology included interviews with 20 pairs of adolescents (aged 11–17) and their parents, analyzing their responses to scam content and examining patterns of critical awareness and parental guidance. Findings Findings suggest that critical awareness and the ability to identify scams improve with age. Primary school individuals rely heavily on parental guidance, whereas adolescents in high schools’ exhibit increased critical thinking, largely because of systematic education about online risks. Parents of younger participants are more concerned and emphasize supervision, while those of older participants display greater confidence in their children’s capabilities. Practical implications This study recommends comprehensive educational programs to develop critical awareness among adolescents. Suggested strategies include implementing school-based curricula on digital literacy, organizing parental workshops to encourage active supervision, and fostering collaboration with social media platforms to promote awareness campaigns. Originality/value This research highlights the changing role of adolescents as both targets and potential spreaders of fraudulent content on social media. This study expands the understanding of how these demographics navigate online risks and contributes to the broader discourse on social media misinformation.
Keywords: scams; social media; online risks; critical thinking; parental perception; fraudulent content